Aspects of solid state formation and properties of Sn(0.9)Ti(0.1)O(2) system doped with CoO and Nb(2)O(5) - Leite, Daniela Russo [UNESP]; Goes, Marcio de Sousa [UNESP]; Bueno, Paulo Roberto [UNESP]; Varela, José Arana [UNESP]; Paiva-Santos, Carlos de Oliveira [UNESP]; Cilense, Mario [UNESP] (J C P D S-int Centre Diffraction Data, 2008)
The effect of calcination temperature during the formation of the solid solution Sn(0.9)Ti(0.1)O(2) doped with 1.00 mol % CoO and 0.05 mol % Nb(2)O(5) is presented. The structural characteristics of this system were studied using X-ray diffraction, and the changes in phase formation were analyzed using the Rietveld method. With an increase in calcination temperature, there is increasing miscibility of Ti into the (Ti,Sn)O(2) phase and near 1000 degrees C, and the remaining TiO(2) (anatase) was transformed into the rutile phase. The sintering process, monitored using dilatometry, suggests two mass transport mechanisms, one activated close to 900 degrees C associated with the presence of TiO(2) (anatase) and the second mechanism, occurring between 1200 and 1300 degrees C, is attributed to a faster grain boundary diffusion caused by oxygen vacancies. (C) 2008 International Centre for Diffraction Data.
Keywords: electronic materials; SnO(2); TiO(2); X-ray diffraction; Rietveld refinement